PENGARUH PELATIHAN DAN KARAKTERISTIK INDIVIDU TERHADAP KINERJA DIMEDIASI OLEH KOMPETENSI PEGAWAI BADAN PENANGGULANGAN BENCANA DAERAH (BPBD) KOTA BATU - suhartono suhartono (MAGISTER MANAJEMEN UNISMA, 2020)
The purpose of this study is to measure and analyze whether there is influence of training and individual characteristics of employee competence, the effect of training, individual characteristics and competence on employee performance, and the indirect influence of training and individual characteristics on employee performance is mediated by the competence of employees in the environment Regional Disaster Management Agency (BPBD) Batu City.The population used in this study is all employees in the environment BPBD Kota Batu by using the census method is to take all existing employees as respondents by distributing questionnaires. This research uses descriptive method of analysis and verification with qualitative approach, and using path analysis. In this research it can be seen that there is influence of training on employee competence of 0,025 and individual characteristics to employee competence equal to - 0,051, influence of training to employee performance equal to 0,196, individual characteristic to employee performance 0,455 and competence to employee performance equal to 0,053, Direct training on the performance of employees mediated by the competence of employees in the environment BPBD Kota Batu is 0.196 + 0.0013 = 0.197 and indirect influence of individual characteristics on the employee performance mediated by the competence of employees in the environment BPBD Kota Batu is 0.455 + 0.024 = 0.479. Keywords: training, individual characteristics, competence and performance.